Standardisation of partial strength connections of extended end–plate connections for trapezoid web profiled steel sections - Md. Tahir, Mahmood; Sulaiman, Arizu (Construction Research Institute of Malaysia (CIDB), 2008)
Traditionally, connections are usually classified as pinned or rigid although the actualbehaviour is known to fall between these two extreme cases. The use of partial strength or semi-rigid connections has been encouraged by codes and studies on the matter known as semi-continuous construction have proven that substantial savings in steel weight of the overall construction. The objective of this paper is to develop a series of standardised partial strength connections tables of extended end-plate connections for trapezoidal web profiled steel (TWP) sections. The range of standard connections presented in tabulated form is limited to eight tables comprised of different geometrical aspects of the connections. These tables could enhance the design of semi-continuous construction of multi-storey braced steel frames. The connections are presented in the form of standardised tables which include moment capacity and shear capacity after considering all possible failure modes. A method proposed by Steel Construction Institute (SCI) which take into account the requirements in Eurocode 3 and BS 5950:2000 Part 1 were adopted to predict the moment capacity and shear capacity in developing the tables. A series of tests have been carried out to validate the results of the standardised tables. The test results showed good agreement between theoretical and experimental values. It can be concluded that the proposed standardised tables for TWP sections is suitable to be used in the design of semi-continuous construction.